DATA CENTER THERMAL AND MOISTURE MONITORING SYSTEM WITH INTELLIGENT PREDICTION - MAHADI, NURIKA THAQIFAH (IRC, 2020)
Data center plays a huge role in every organization. It stores every data of the organization and performs all processes and operations. This makes it important to have a good monitoring system for the data center to ensure that it is well-maintained. This paper focused on the implementation of a data center monitoring system that comes with an intelligent prediction. This system aims to assist IT personnel to have a better overview of the environmental temperature and humidity level of the data center in real-time manner. The intelligent prediction will include a forecast of the next 7 days of the data retrieved from the datasets. IT personnel will be able to construct a failover plan in case of an abnormal change in temperature and humidity. The proposed system was developed using Raspberry Pi 3 Model B+ with the aid of DHT22 – a sensor that can detect both temperature and humidity. The real-time data was sent to Microsoft Power BI to be visualized in a graphical form. All the data was recorded in a Comma-separated Value (CSV) file. These data were daily imported to Power BI for visualization on daily analysis. Every week, the data was forecasted using a built-in predictive analytics tool in Power BI.